2008
DOI: 10.1063/1.2885091
|View full text |Cite
|
Sign up to set email alerts
|

Surface proximity and boron concentration effects on end-of-range defect formation during nonmelt laser annealing

Abstract: The effects of surface proximity and B concentration on end-of-range defect formation during nonmelt laser annealing in preamorphized silicon have been studied. These effects were analyzed by observing the activation and diffusion of an ultrashallow B implant, using Hall effect and secondary ion mass spectrometry measurements. By adjusting the preamorphizing implant and laser annealing conditions, B deactivation and diffusion were minimized, resulting in a sheet resistance of ϳ600 ⍀ / sq with a 16 nm junction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In contrast, the much shorter duration time of excimer laser annealing (<200 ns) is comparable to that of some basic point-defect related phenomena, such as Si interstitial diffusion and clustering 11 , which makes the defect-formation mechanism itself questionable in this annealing regime. In addition, most of the existing studies of defect formation in laser annealed silicon have been carried out in preamorphised structures: (i) after non-melt anneals, conventional endof-range defects ({311} defects and {111} DLs) have been observed [12][13][14] ; (ii) in the case of melt laser annealing, the defects nature depends on the position of the melt front with respect to the amorphous/crystalline, a/c, interface (stacking faults are observed in the case of incomplete melting of the preamorphised layer, 15 defect-free crystalline silicon is found when melting goes beyond the a/c interface 16 ).…”
mentioning
confidence: 99%
“…In contrast, the much shorter duration time of excimer laser annealing (<200 ns) is comparable to that of some basic point-defect related phenomena, such as Si interstitial diffusion and clustering 11 , which makes the defect-formation mechanism itself questionable in this annealing regime. In addition, most of the existing studies of defect formation in laser annealed silicon have been carried out in preamorphised structures: (i) after non-melt anneals, conventional endof-range defects ({311} defects and {111} DLs) have been observed [12][13][14] ; (ii) in the case of melt laser annealing, the defects nature depends on the position of the melt front with respect to the amorphous/crystalline, a/c, interface (stacking faults are observed in the case of incomplete melting of the preamorphised layer, 15 defect-free crystalline silicon is found when melting goes beyond the a/c interface 16 ).…”
mentioning
confidence: 99%
“…The same study showed poorer results using preamorphization implants, although the comparison was somewhat approximate because the preamorphization energies used produced deeper amorphous layers than the B 18 H 22 implants. In order to make a direct comparison with the molecular implant results, we now revisit recently reported observations using preamorphization implants with a range of incident energies [4].…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…, to show all EOR dislocation loops that are present (Ref. [4]). In case (a), 10 keV Ge, a significant number of loops are present after laser anneal.…”
Section: Comparison Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations